Transference and Countertransference in Counseling - Ice Desvikayati; Yeni Karneli; Mudjiran; Ramdani (Journal Of Psychology, Counseling And Education, 2025)
In the counseling process, transfer and countertransfer are important psychological phenomena. When clients unconsciously project their feelings, hopes, or past experiences onto the counselor, this is called transference. On the other hand, the counselor's emotional reaction to the client which is influenced by the counselor's personal experiences is called countertransference. In a counseling relationship, this phenomenon can be both a challenge and an opportunity. This article discusses the ideas, dynamics, and effects of transference and countertransference on counseling effectiveness. The focus is on how important self-awareness, reflection skills, and supervision are to managing these two phenomena in a beneficial way. To find important problems that influence clients in managing transference, counselors must understand the client's emotional and behavioral patterns. To avoid mistakes that can occur in the counseling relationship, managing countertransference requires that counselors be aware of their own biases and emotional reactions.